Evaluating the Intellectual Structure of the Knowledge Base on Transformational School Leadership: A Bibliometric and Science Mapping Analysis - Turgut Karakose; Tijen Tülübaş; Stamatios Papadakis; Ramazan Yirci (MDPI AG, 2023)
Transformational leadership has been persistently studied in the educational administration field considering that it can be a viable tool to respond to the increasing demands on school systems for greater effectiveness. As a result, a rich knowledge base has been accumulated. Our study aims to investigate this knowledge base by combining bibliometric and science mapping analysis so as to exhibit its intellectual and conceptual architecture, and to reveal the strategic themes that emerged during the scientific evolution of transformational school leadership (TSL). 300 articles retrieved from the Scopus database were included in the analysis. The thematic evolution analysis was performed using the SciMAT software over three time periods: the Incubation Period (1989-2009), the Development Period (2010-2020), and the Maturation Period (2021-2022). The findings show that research during the Incubation Period mostly attempted to conceptualize TSL while it mostly focused on principals, instructional leadership, and self-efficacy during the Development Period. The mentoring theme emerged during the first period but disappeared later without being fully-developed. Teacher leadership emerged as a weakly-addressed theme during all periods. Work-family conflict and digital competencies were the two prominent themes during the Maturation Period while online learning and learning culture were found to be the emerging themes. The findings suggest significant implications for the sustainable development of the TSL research field.